2019
DOI: 10.1038/s41598-019-44147-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Role of Oxidative Stress and Blood-Brain Barrier Permeability as Injury Mechanisms in the Acute Pathophysiology of Blast-induced Neurotrauma

Abstract: Blast-induced traumatic brain injury (bTBI) has been recognized as the common mode of neurotrauma amongst military and civilian personnel due to an increased insurgent activity domestically and abroad. Previous studies from our laboratory have identified enhanced blood-brain barrier (BBB) permeability as a significant, sub-acute (four hours post-blast) pathological change in bTBI. We also found that NADPH oxidase (NOX)-mediated oxidative stress occurs at the same time post-blast when the BBB permeability chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 65 publications
1
40
0
1
Order By: Relevance
“…Given the increasing awareness that neuroinflammation can interact with other aspects of TBI pathophysiology, it is likely that alterations or manipulation of the NLRP3 inflammasome will have multiple pathophysiological consequences. For example, recent studies have found that a relationship exists between neuroinflammation, oxidative stress, and blood-brain barrier permeability after TBI [84,108,109]. The involvement of the NLRP3 inflammasome in these interactions is not yet known; however, MCC950 treatment TBI was found to reduce the extent of blood-brain barrier damage and apoptosis in the acute stages after in TBI mice [70].…”
Section: Effect Of Nlrp3 Inflammasome On Tbi Pathophysiologymentioning
confidence: 99%
“…Given the increasing awareness that neuroinflammation can interact with other aspects of TBI pathophysiology, it is likely that alterations or manipulation of the NLRP3 inflammasome will have multiple pathophysiological consequences. For example, recent studies have found that a relationship exists between neuroinflammation, oxidative stress, and blood-brain barrier permeability after TBI [84,108,109]. The involvement of the NLRP3 inflammasome in these interactions is not yet known; however, MCC950 treatment TBI was found to reduce the extent of blood-brain barrier damage and apoptosis in the acute stages after in TBI mice [70].…”
Section: Effect Of Nlrp3 Inflammasome On Tbi Pathophysiologymentioning
confidence: 99%
“…In our study, we investigate whether the kinetic energy transferred to the brain (i.e., a body internal structure) through the blood (i.e., the fluid medium) could potentially damage the brain vessels and tissues. Surprisingly, despite extensive experimental evidence supporting varying degrees of cerebrovascular pathology in animals exposed to whole-body blast (Gama Sosa et al, 2013Kuriakose et al, 2018Kuriakose et al, , 2019Logsdon et al, 2018;Heyburn et al, 2019), the existence of such a blood surge has not been thoroughly investigated, possibly because of the challenges in measuring hemodynamic parameters, such as mass flow rate and flow-velocity fields, in the cerebral vasculature during a blast exposure. As an alternative, and complementary to animal experimentation, high-fidelity, fluidstructure interaction (FSI) computational models allow for the characterization of such hemodynamic parameters and the estimation of biomechanical responses (e.g., the wall shear stress) in the cerebral vasculature, which could help elucidate whether blast exposure targeting only the torso can generate a noticeable blood surge to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Across the TBI spectrum, mitochondrial dysfunction and impaired cell membrane homeostasis within neuronal, axonal, and glial cells can exacerbate neurotransmission impairment. Biomechanical forces deforming brain cells during TBI can damage axons and increase BBB permeability, both of which can be further aggravated by unregulated free radicals (Kuriakose et al., 2019; Ljubisavljevic, 2016). Compromised tight junctions between endothelial cells within the BBB results in cerebral edema further compromising neurotransmission (Kenzie et al., 2018; Luissint et al., 2012).…”
Section: Discussionmentioning
confidence: 99%